Regulation of blood–testis barrier by actin binding proteins and protein kinases. Issue 3 (March 2016) - Li, Nan; Tang, Elizabeth I; Cheng, C Yan
Abstract : The blood–testis barrier (BTB) is an important ultrastructure in the testis, since the onset of meiosis and spermiogenesis coincides with the establishment of a functional barrier in rodents and humans. It is also noted that a delay in the assembly of a functional BTB following treatment of neonatal rats with drugs such as diethylstilbestrol or adjudin also delays the first wave of spermiation. While the BTB is one of the tightest blood–tissue barriers, it undergoes extensive remodeling, in particular, at stage VIII of the epithelial cycle to facilitate the transport of preleptotene spermatocytes connected in clones across the immunological barrier. Without this timely transport of preleptotene spermatocytes derived from type B spermatogonia, meiosis will be arrested, causing aspermatogenesis. Yet the biology and regulation of the BTB remains largely unexplored since the morphological studies in the 1970s. Recent studies, however, have shed new light on the biology of the BTB. Herein, we critically evaluate some of these findings, illustrating that the Sertoli cell BTB is regulated by actin-binding proteins (ABPs), likely supported by non-receptor protein kinases, to modulate the organization of actin microfilament bundles at the site. Furthermore, microtubule-based cytoskeleton is also working in concert with the actin-based cytoskeleton to confer BTB dynamics. This timely review provides an update on the unique biology and regulation of the BTB based on the latest findings in the field, focusing on the role of ABPs and non-receptor protein kinases.